PENGARUH GAYA HIDUP, HARGA DAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN SEPEDA LISTRIK (STUDI KASUS PELANGGAN DI TOKO SINAR BIKE KABUPATEN MERANGIN) - Anggraini, Rita (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aimsto analyze the influence of lieftyle, Rice And Product Quality On Electric Bicycle Customer Satisfaction (Case Study Of Customers At The Sinar Bike Shop, Merangin Regency). In the modern era, transportation is a means of supporting human daily life. This reseaech isa quantitative method with data collection using a total of 153 customers at the sinar bike shop. Validity test analysis technique, correlation reabiliti test of classical assumtionsmultiple linier regresioin analysis and hypothesis testing. The result of the research show that lifestyle does not partially have appositive and significan effect on customer satisfaction (t = 1.033), (0,001<0,05). While price positive and significant effect on customer statisfaction (t = 3.089), (0.000 < 0.05), while product quality has appositive and significant effect on customer satisfaction (t =7.314), (0.000 < 0.05)simultaneously, these tree variable have a significant effect oncustomer satisfaction (F = (63.142), (0.000< 0.05). adjuster R is 0.551. whinch means all independent variable can influence 50,5% while 40,5% can be influenced by factors in conclusion, this research confirms that price anad product quality play an importan role in sahping customer satisfaction at the Sinar Bike Shop in Merangin district, while lifestyle doesnothave a significat influence.